Plan de negocios, mediante la aplicación de la metodología de Canvas, para proponer la creación de la agencia operadora de turismo Amazónian Travel, en el cantón Shushufindi - Cacoango Cacoango, Martha Mercedes (2016)
The research is the development in the province of Sucumbíos, Shushufindi Cantón, it raises develop a proposal for the creation of an operating agency of tourism called Amazónian Travel. The need of the people, national and international tourists to know the natural and cultural attractions found in the sector helped create the Tour operator, thus helping to socio-economic growth of the population. To conduct field research was used the methodology of the situational analysis of the area which gave us information about the study area analyzing different factors including infrastructure, natural aspects, socio-cultural, economic, agricultural, social, and tourism. Haming seen the feasibility of the situational study area the KEDS methodology was used, thereby enabling developing the business plan where the results of the tabulation of surveys which allowed developing market segmentation was obtained, the value proposition, distribution channels, customer relationships, revenue streams, key activities, key resources, key partners and infrastructure costs. With all the information collected could develop the corporate image and the development of tourist packages. With the results we proceeded to establish the creation of the operating agency Amazónian Travel obtaining all requirements such as: registration for travel agencies, recording sheet SRI, municipal license and certificate for operating permit by the Body Shushufindi Cantón fire Department.